A CASE OF NECK LARYNGOGENIC PHLEGMON SURGICAL TREATMENT WITH LEFT OROPHARYNX ANTEROLATERAL WALL PERFORATION COMPLICATED BY MEDIASTINITIS - Khoroshun, E.M.; Makarov, V.V.; Nehoduiko, V.V.; Zhuzhoma, M.S.; Otchyk, О.О.; Tertyshnyi, S.V.; Vastyanov, R.S. (World of Medicine and Biology, 2025)
The purpose of the study was to demonstrate the features of diagnosis and surgical treatment in the case of laryngogenic phlegmon of the neck with perforation of the anterolateral wall of the oropharynx on the left, complicated by mediastinitis. Patient K., 42 years old, first felt a sore throat while on vacation. Three days later, he was hospitalized. Surgical treatment, on the day of hospitalization, was performed in the following scope: bilateral colotomy. Opening of neck phlegmon. Drainage of retropharyngeal and retroesophageal spaces, drainage of the postero-superior, antero-superior, and antero-inferior mediastinum. Kader gastrostomy. The final diagnosis was the following: the neck laryngogenic phlegmon with left oropharynx anterolateral wall perforation, abscess of the left retropharyngeal space, total frontal and back upper mediastinitis with severe complications concerning cardiovascular and respiratory systems pathology. Subsequently, staged surgical interventions were performed. Authors attracted attention to the fact that neck laryngogenic phlegmon requires immediate diagnostic intervention and timely treatment, as it can lead to serious complications. Mediastinitis, as a complication of the neck laryngogenic phlegmon, is a hazardous condition with a high risk to the patient's life. The authors concluded that treatment of neck laryngogenic phlegmon complicated by mediastinitis should be comprehensive and include broad-spectrum antibiotic therapy, surgical drainage, and intensive support of the patient's vital functions.
Keywords: laryngogenic phlegmon of the neck; total mediastinitis; perforation; surgical intervention; treatment